2(4x-3)+2x=2z+18

Simple and best practice solution for 2(4x-3)+2x=2z+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x-3)+2x=2z+18 equation:


Simplifying
2(4x + -3) + 2x = 2z + 18

Reorder the terms:
2(-3 + 4x) + 2x = 2z + 18
(-3 * 2 + 4x * 2) + 2x = 2z + 18
(-6 + 8x) + 2x = 2z + 18

Combine like terms: 8x + 2x = 10x
-6 + 10x = 2z + 18

Reorder the terms:
-6 + 10x = 18 + 2z

Solving
-6 + 10x = 18 + 2z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 10x = 18 + 6 + 2z

Combine like terms: -6 + 6 = 0
0 + 10x = 18 + 6 + 2z
10x = 18 + 6 + 2z

Combine like terms: 18 + 6 = 24
10x = 24 + 2z

Divide each side by '10'.
x = 2.4 + 0.2z

Simplifying
x = 2.4 + 0.2z

See similar equations:

| -3(6x-1)+12x-15=-30 | | 100(x+-3)=450+-50x | | 4+8(3k-8)= | | 0.55x+6.99=11.99 | | -8.5c+5.5c=-25.5 | | 49x^4-121=0 | | 20+(8q-11)=-12 | | (16x+2y)+(46x+25y)= | | 6(-x-4)-3(8x-8)= | | 5-4x=-2x-3x | | 6x+9=3x+42 | | 9+(4z-2)=-(5z+5)+1 | | -15=-1+r | | 5-4x=-2z-3x | | 6w-11=3w+1 | | (42x+63y)+(39x-13y)= | | =1.6E+60 | | 2.7=5.4x-8.1y | | 4x-1.5x=50 | | 1.99m+45=68.88 | | Y=44+30 | | -12(-4x+6)-x+7-(-9x)= | | 1.99+45=68.88 | | 16+m-3=78 | | -3x+x=-7x-11 | | y+9=2(x+-5) | | .8(5+x)=5.2 | | R^4-16r^2=0 | | 324=n+112+25 | | f(x)=3x^2-x+10 | | 3(a+2)-7=13-(5b) | | 6x-2+17=8x+2 |

Equations solver categories